Monstrous : the lore, gore, and science behind your favorite monsters - Beccia, Carlyn (Carolrhoda Books, 2019)
Explores the historic and scientific origins of monsters such as vampires, werewolves, zombies, and Godzilla. Includes color illustrations, timelines, and resources for further information.